2012
DOI: 10.1037/a0025836
|View full text |Cite
|
Sign up to set email alerts
|

How category learning affects object representations: Not all morphspaces stretch alike.

Abstract: How does learning to categorize objects affect how we visually perceive them? Behavioral, neurophysiological, and neuroimaging studies have tested the degree to which category learning influences object representations, with conflicting results. Some studies find that objects become more visually discriminable along dimensions relevant to previously learned categories, while others find no such effect. One critical factor we explore here lies in the structure of the morphspaces used in different studies. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
102
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 39 publications
6
102
0
Order By: Relevance
“…Having said that, the current morph method does follow Folsteinʼs morph model of a factorial morph space. Such a morph space has been shown to increase discriminability along the relevant dimensions (Folstein et al, 2012). In this study, we manipulated the features of the fish independent of each other.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Having said that, the current morph method does follow Folsteinʼs morph model of a factorial morph space. Such a morph space has been shown to increase discriminability along the relevant dimensions (Folstein et al, 2012). In this study, we manipulated the features of the fish independent of each other.…”
Section: Stimulimentioning
confidence: 99%
“…Recently, Folstein, Gauthier, and Palmeri (2012) proposed two different methods of morphing stimuli to create different category members, the blended and factorial models. In both cases, the morph space between the prototypes is shaped as a tetrahedral volume.…”
Section: Stimulimentioning
confidence: 99%
“…Several studies have demonstrated that whether CP is observed at all depends on various factors including (1) the availability of verbal labels during perceptual testing [9], (2) the particular kind of perceptual assessment used to determine whether CP is present [10], and (3) how stimulus morphspaces are created [11]. However, few studies have reported differences in the kind of CP effect observed based on experimental manipulations, though there are exceptions.…”
mentioning
confidence: 90%
“…According to some theories of object recognition, object representations in visual cortex are not systematically influenced by the way those objects have been categorized (e.g., Riesenhuber & Poggio, 1999), with fMRI modulation according to learned category appearing in frontal areas but not in visual areas (e.g., Jiang et al, 2007). By contrast, Folstein et al (2012) appeal to the theories of categorization that place significant emphasis on the role of selective attention (e.g., Kruschke, 1992;Nosofsky, 1984) or perceptual stretching (e.g., Goldstone, 1994) of object dimensions relevant to learned categories (see Gauthier & Palmeri, 2002). Many experiments studying object categorization use morphing techniques to create continuous spaces of complex objects.…”
mentioning
confidence: 99%
“…Many experiments studying object categorization use morphing techniques to create continuous spaces of complex objects. Folstein et al (2012) show that the details of how those morphspaces are created matter a lot. When morphspaces are created by factorially combining morphlines (Goldstone & Steyvers, 2001), perceptual stretching along category-relevant object dimensions is observed.…”
mentioning
confidence: 99%